Environmental Pollution from Cane Sugar Factories: A Study of Chemical Features Variations in the Wastewater - Khair, A. S. E.; Elfaig, A. H. I.; Yassen, M. E.; Purwanto, P.; Sunoko, H. R. (Jurnal Pendidikan IPA Indonesia, 2023)
Sugar industry processes release large amounts of wastewater and pollution concentrations. This study focuses on environmental pollution produced by a cane sugar factory (Sampling Assalaya factory) with particular emphasis on the chemical properties of wastewater as an essential feature identifying water pollution in the study area. The study aims to analyze wastewater’s chemical features and disparity based on the Sudanese Standards and Metrology Organization (SSMO) standards. The systemic random sampling method collected twenty samples for each parameter (pH, Total Hardness, PO4, BOD, and COD). Analyses were conducted in the laboratory according to the standard methods for examining water and wastewater (USA). Results revealed significant variations in wastewater features at different sampling sites as pH values ranged between 4.55 to 8.39 and PO4 ranged between 0.097 ppm to 670 ppm in the selected sites. Results also pointed out that Total hardness ranged between 50ppm to 470ppm, BOD ranged between 15ppm to 390ppm, whereas the COD in 80% of the tested samples exceeded the SSMO standard (150ppm). The article concluded that these levels are highly exceeding the recommended level by SSMO. The leading causes of such alarming pollutant levels are related to the effluent of the Assalaya sugar factory in the study area. To reduce such effluent pollution levels, suggestions are made for the Assalaya cane sugar factory to treat its effluent by introducing appropriate technology and methods, such as anaerobic treatment. The Assalaya sugar factory ought to keep up with the transformation to green production as an integral part of its policy to achieve sustainability.